Value enhancement of fermented ground pork product using Y-aminobutyric acid producing starter lactic acid bacteria - Anussara Ratanaburee (Prince of Songkla University, 2015)
Thesis (Ph.D., (Microbiology ))--Prince of Songkla University, 2014